Improved Mathematical Representation of Students With The Open-Ended Approach - M. Syahdan Tarigan; Zainal Azis; Marah Doli Nasution (JMEA : Journal of Mathematics Education and Application, 2022)
The innovative design of this study was to create a non-equivalent pre-test and post-test control group. The population of this study includes all Class IX students at PGRI 3 Medan Private Secondary School, consisting of 116 students, and the selected sample consists of two classes. The tools used are descriptive forms of mathematical representation tested and validated. The results of these studies showed that students who received open methods were much better at expressing themselves accurately than students who received traditional methods. Show that the open-ended approach can improve students' mathematical expression, even if the results are suboptimal because students' grades are still poor. This happens because the open-ended approach allows students to solve problems in different ways and create multiple representations of the problem.